Assessing and Evaluating Ḥadith, its Value, Significance, Authority and Authenticity in Islamic Thought - Nisar, Farhat; Bukhari, Sayyed Abdul Ghaffar (Journal of Islamic and Religious Studies, 2017)
Qur’an and Ḥadith as fundamental and primary sources of Shariah stand as hall mark of Islam. Ḥadith called traditions as the second fundamental source of Islam embodies sayings, actions and expressions of Prophet Muhammad (SAW) explicit or implicit. Mainly there have been two trends of rejecting the status of Ḥadith. One is rejecting the authority of Ḥadith and other rejects the authenticity of Ḥadith especially “Khabar-al-wahid” or solitary tradition. Other group does not completely reject the authority of Ḥadith rather text of Ḥadith especially in case of weak traditions. This paper discuss the opinion of rejecters of Ḥadith and contribution of Muslim scholars along with their arguments from Qur’an and Sunnah of Prophet Muhammad (SAW) to highlight the importance and significance of authority and authenticity of Ḥadith in all disciplines of Islamic thought.